Effects of soaking periods and adhesive concentrations on the properties of phenol formaldehyde resin treated oil palm wood - Ismail, Puteri Nur Khairunnisha; Bakar, Edi Suhaimi; Ling, Rachel Joanes; Halis, Rasmina; Choo, Adrian Cheng Yong (Universiti Putra Malaysia Press, 2017)
Oil palm (Elaeis guineensis Jacq.) is one of the most important and under-utilised non-wood biomass in Malaysia. This study examined the effect of low molecular weight phenol formaldehyde (Lmw-PF) resin impregnation on the mechanical and physical properties of oil palm trunk wood. The oil palm wood was treated using the following steps: by drying, resin impregnation, soaking and re-drying of specimens using different resin concentrations and treatment times. The determination of the modulus of elasticity, modulus of rupture and dimensional stability of treated oil palm wood were carried out using British standards. Results indicated that both resin concentration and soaking time significantly enhanced dimensional stability of the treated oil palm wood. Water absorption and thickness swelling of the treated wood displayed reduction with different soaking periods and resin concentrations with the best results of 7.37% and 5.08% respectively. Soaking had a significant effect on the bending properties of treated oil palm wood and showed 1.5 and 1.8 times improvement in modulus of elasticity and modulus of rupture respectively. It can be thus concluded that resin impregnation followed by soaking of oil palm wood is a viable method to improve its overall physical and mechanical properties as well as its dimensional stability.